Experimental and numerical investigations on the seismic behavior of bridge piers with vertical unbonded prestressing strands - Sun, Z.; Wang, D.; Bi, Kaiming; Si, B. (2015)
In the performance-based seismic bridge design, piers are expected to undergo large inelastic deformations during severe earthquakes, which in turn can result in large residual drift and concrete crack in the bridge piers. In this paper, longitudinal unbonded prestressing strands are used to minimize residual drift and residual concrete crack width in reinforced concrete (RC) bridge piers. Seven pier specimens were designed and tested quasi-statically and the numerical simulations were carried out. The effectiveness of using vertical unbonded prestressing strands to mitigate the residual drift and concrete crack width of RC bridge piers are examined and discussed in detail. It is found that the residual drift and residual concrete crack width of the piers can be reduced significantly by using the prestressing strands. Moreover, the strands can increase the lateral strength of the piers while have little influence on the ductility capacity of the piers. The hysteretic curves, residual drifts and strand stress of the piers predicted by the numerical model agree well with the testing data and can be used to assess the cyclic behavior of the piers.